Design of a PV-diesel hybrid system with unreliable grid connection in Kampung Lb Johnson Village, Malaysia - Almajdup, Salleh A.A (2018)
The development of the current,existing and unreliable source of energy became necessary in the last decade,due to the huge demand on the electrical energy that caused by the developed technologies and electrical applications.In this study the integration of the renewable energy resources - solar Photovoltaic (PV) generators into an existing diesel generator and unreliable grid connection system is discussed and explained.The proposed location is Kampung LB Johnson villages,Negeri Sembilan,Malaysia.The main objective of this work is to develop,improve,and implement the optimal hybrid PV/diesel generator/battery hybrid system over the current unreliable grid connection.Firstly,the inclusion of the site location and metrological data is carried out,then the estimation of the load profile is performed for 120 households that locate at the proposed location. Secondly,the choosing of the proposed components of the system parts are also performed which includes PV arrays, diesel generators,fuel prices,battery banks and system power convertor.Thirdly,the pre-design step which includes finding all possible,existing and prospective scenarios are designed and prepared.Finally,the simulation of all of the proposed designs are carried out in deep details using HOMER software.The performance of all systems is driven based on deep analysis of all technical,economical,and environmental aspects.In addition,each system is compared to all other systems in order to find the optimal design with respect to the current existing diesel generator/grid system.Meanwhile, four different systems were choosing which includes.The existing diesel generator/grid,PV /battery/grid,PV/diesel generator/battery,PV/battery,and PV/diesel generator/battery/grid hybrid system.The result indicates that the PV/diesel generator/battery/grid hybrid system shows the best behaviour,sizing efforts,techno-economic, and a very good environmental performance over all systems.This system is choosing to be the optimal system by including the best Net Present Cost (NPC) RM6341312.46 and a very good Cost of Energy (COE) 1.226 RM/kWb,and seem to be promising for updating the current standalone (unreliable) systems.However,although the PV/diesel generator/battery/grid scenario shows a very good environmental performance,the 100% renewable energy system (PV /battery) trends to have the best environmental effects towards the surrounding environment by realising zero C02 emissions.Unfortunately,the PV /battery scenario have the highest NPC and COE.The results also informed that using hybrid system in power generation and updating the unreliable standalone mini-grid system would result in improving the general performance of the system,reducing the fuel consummation, fuel cost,and harmful C02 emissions.However,due to the current high prices of the renewable energy systems such as PV and batteries,the total replacement of the existing system seems to be economically impractical.But,the current developed technology seems to be promising to reduce these prices in the near future.